BOVINE MASTITIS CAUSED BY Bacillus spp. IN KHARTOUM STATE, SUDAN - Rabie Mohammed Salih, Reem; Osman Ahmed, d A/ Basit (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted in Khartoum state, Sudan, between 2006- 2008. Hundered milk samples were collected from cows with clinical mastitis. The percentage of acute mastitis 55% acute mastitis, 44% chronic mastitis and 1% gangrenous mastitis. Milk samples were cultured in Blood agar and MacConkey´s agar for 24 hours at 37º C. The isolation of Bacillus spp. amounted to 74% ; these constituted 31% Bacillus coagulans, 11% B. cereus, 9% B. subtilis, 9% B. licheniformis, 4% B. circulans, 3% B. mycoides, 3% B. amyloliquefaciens, 2% B. lentus, and 2% B. megaterium.